1990
DOI: 10.1111/j.1600-0773.1990.tb00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Bovine Mesenteric Arteries by Glyceryl Trinitrate and Other Nitro‐Compounds: Evidence for Partly Different Mechanisms of Action

Abstract: The effect of pertussis toxin (PTX) and the cyclic GMP lowering agent LY83583 on the relaxatory response induced by glyceryl trinitrate (GTN), isosorbide dinitrate (ISDN), isosorbide-5-mononitrate (IS-5-MN) and sodium nitroprusside (SNP) in bovine mesenteric artery (BMA) was investigated. Pretreatment with PTX (100 ng/ml; 2 hr induced a 100-fold right shift of the concentration-effect curve for GTN, while no effect on the relaxatory response elicited by ISDN, IS-5-MN or SNP was seen. The relaxatory effect of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In in vitro studies, pretreatment with pertussis toxin induced a 100-fold right shift of the concentration-effect curve for GTN, suggesting the involvement of a G protein. 31 Baseline GTNinduced relaxation was not significantly different between genotypes. After metabolic improvement, however, the response to GTN was enhanced in carriers of the 825T allele.…”
Section: Discussionmentioning
confidence: 83%
“…In in vitro studies, pretreatment with pertussis toxin induced a 100-fold right shift of the concentration-effect curve for GTN, suggesting the involvement of a G protein. 31 Baseline GTNinduced relaxation was not significantly different between genotypes. After metabolic improvement, however, the response to GTN was enhanced in carriers of the 825T allele.…”
Section: Discussionmentioning
confidence: 83%
“…The key mediator of erection NO leads to an activation of the guanylate cyclase catalysing the formation of cyclic guanosine monophosphate (cGMP) from guanosine triphosphate, which results in the relaxation of smooth muscle cells promoting the blood flow into the corpora cavernosa (Rajfer et al, 1992;Andersson & Wagner, 1995). One study alludes to the fact that cGMP exerts its smooth muscle relaxing effect partially via Gprotein coupled signal transduction (Torfgard et al, 1990). This might explain the improved response of patient's genotype TT to sildenafil .…”
Section: Discussionmentioning
confidence: 97%
“…Several reports have documented enhanced G protein-mediated signal transduction in patients carrying the T allele of GNB3 (18). Torfgard et al reported that glycerol trinitrate (GTN) relaxes vascular smooth muscle cells partially via G protein-dependent mechanisms (19). The nitric oxide (NO)/cyclic GMP pathways are altered in diabetic patients who carry the T allele (20), and the degree of improved insulin sensitivity and the vasodilatory response to GTN are much larger in T allele carriers (14).…”
Section: Discussionmentioning
confidence: 99%